58 ECG Electrode Positioning – Luck or Judgment?. (3rd June 2016) - Kishto, Oomesh; Pope, Michael; Hobson, Alexander; Petley, Graham; Evans, Michelle; Bain, Richard
Abstract : Introduction: Electrocardiography is the most common tool used to assist in the evaluation of cardiac disease. A standardised technique is crucial to allow accurate interpretation and comparison of serial tracings. Guidelines are produced by The American Heart Association and the Society for Cardiological Science and Technology. We sought to evaluate knowledge of precordial lead positioning amongst healthcare staff involved in the emergency care of patients with suspected cardiac disease. Methods: 106 staff of various groups were asked to identify the correct locations for precordial lead position on a schematic of the chest wall. Results were analysed according to distance from the correct position in millimeters (mm) and a mean distance across all leads was calculated. Cardiac physiologists receive the most robust training in ECG acquisition and secondary analysis compared positions identified by other healthcare staff to physiologists. The 95% confidence interval for the physiologists' lead positions was calculated and then used to define the correct position for a comparison against other professional groups. Results: Of the 106 staff members recruited, 9% were cardiac physiologists, 12% cardiographers, 11% cardiology nurses, 11% cardiology consultants or registrars, 18% non-cardiology nurses, 11% healthcare support workers, 13% non-cardiology physicians, and 12% paramedics. Knowledge of lead position was highly variable with many staff suggesting positions a significant distance from the guideline recommendations. Figure 1 represents the distribution of positions identified for each precordial lead. All of the leads tend be placed higher up the chest wall with V1, V2 and V6 also tending to be more lateral. Cardiac physiologists were the most accurate with a mean distance from the correct position across all leads of 6.7mm. Cardiographers performed similarly well with a mean distance of 6.9mm. Results for cardiology staff nurses, paramedics, non-cardiology physicians and non-cardiology staff nurses were 13.3, 13.9, 12.7 and 17.7mm respectively. Although healthcare support workers were the furthest away at 19.9mm, cardiologists were on average 17.2mm away. Secondary analysis compared all groups to cardiac physiologists. Figure 2 represents the percentage of correctly placed electrodes by each professional group. Although cardiographers performed well, cardiologists performed very poorly. Conclusion: These results demonstrate a significant lack of knowledge in the correct technique of ECG acquisition amongst healthcare staff outside of physiologists and cardiographers. Most notably, cardiology physicians appeared to be the least knowledgeable. This has the potential to result in artifactual changes in the ECG, particularly in respect of R wave progression, ST, and T wave morphology that could lead to misdiagnosis and administration of potentially harmful treatments. Further training is required and consideration of certification to ensure standardised practice.